Improving Safety of Preemptive Therapy with Oral Valganciclovir for Cytomegalovirus Infection after Allogeneic Hematopoietic Stem Cell Transplantation. (3rd December 2012) - Barkam, Corinna; Kamal, Haytham; Dammann, Elke; Diedrich, Helmut; Buchholz, Stefanie; Eder, Matthias; Krauter, Jürgen; Ganser, Arnold; Stadler, Michael
Abstract : Valganciclovir (VGC), an oral prodrug of ganciclovir (GCV), has been shown to clear cytomegalovirus (CMV) viremia in preemptive treatment of patients after allogeneic hematopoietic stem cell transplantation (alloHSCT), apparently without significant toxicity. Since VGC obviates hospitalization, it is increasingly being adopted, although not approved, in alloHSCT. When we retrospectively evaluated preemptive treatment with VGC versus GCV, foscarnet or cidofovir, in all 312 consecutive CMV viremias of 169 patients allotransplanted at our institution between 1996 and 2006, we found VGC more efficacious (79%) than non-VGC therapies (69%). The advantage of outpatient VGC, however, was outbalanced by more profound neutropenias (including two cases of agranulocytosis, one with graft loss) requiring subsequent prolonged rehospitalization. Thus, in a second, prospective cohort from 2007 to 2011 (all 202 consecutive CMV viremias of 118 yet older and sicker patients), we implemented twice weekly neutrophil monitoring during outpatient VGC treatment and avoided VGC maintenance therapy. While conserving efficacy (VGC 71%, non-VGC 72%), we could now demonstrate a reduced mean duration of hospitalization with VGC (9 days (0–66)) compared to non-VGC (25 days (0–115)), without any agranulocytosis episodes. We conclude that safe outpatient VGC therapy is possible in alloHSCT recipients, but requires frequent monitoring to prevent severe myelotoxicity.